2021
DOI: 10.1371/journal.pgen.1009123
|View full text |Cite
|
Sign up to set email alerts
|

Independent domains for recruitment of PRC1 and PRC2 by human XIST

Abstract: XIST establishes inactivation across its chromosome of origin, even when expressed from autosomal transgenes. To identify the regions of human XIST essential for recruiting heterochromatic marks we generated a series of overlapping deletions in an autosomal inducible XIST transgene present in 8p of the HT1080 male fibrosarcoma cell line. We examined the ability of each construct to enrich its unified XIST territory with the histone marks established by PRC1 and PRC2 as well as the heterochromatin factors Macro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 65 publications
(98 reference statements)
4
60
0
Order By: Relevance
“…In addition to the well-studied Repeat A region, we also observed that Repeat F and a 3' region were critical for silencing. While those domains were not required for H4K20me1 or CIZ1 recruitment, we previously demonstrated that H3K27me3 enrichment required the Repeat F region, while the 3' region was critical for ubH2A recruitment (13).…”
Section: Western Blottingmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition to the well-studied Repeat A region, we also observed that Repeat F and a 3' region were critical for silencing. While those domains were not required for H4K20me1 or CIZ1 recruitment, we previously demonstrated that H3K27me3 enrichment required the Repeat F region, while the 3' region was critical for ubH2A recruitment (13).…”
Section: Western Blottingmentioning
confidence: 85%
“…1C and Additional le 1: Table S2 (see ref. (13))). The change in allelic ratio caused by each deletion construct was normalized to the change in allelic ratio for Full length XIST and presented as strength of silencing, where a value of 1 indicated comparable silencing to Full XIST and 0 indicated no change in allelic contribution from the pre-induction levels.…”
Section: Western Blottingmentioning
confidence: 99%
See 2 more Smart Citations
“…The well-characterized lncRNAs HOTAIR , ANRIL , XIST and KCNQ1OT1 are able to recruit epigenetic modifiers to specific loci for reprogramming the chromatin state [ 64 , 80 ]. For example, HOTAIR acts as a scaffold for coordinating the targeting of specific repressive, histone-modifying complexes to target loci [ 80 ]; XIST mediates X chromosome inactivation by recruiting repressive histone complexes such as PRC1 and PRC2 [ 81 , 82 , 83 ] and DNA-methylating complex [ 84 ]. Additionally, lncRNAs affect allelic gene expression through imprinting.…”
Section: Functional Roles Of Lncrna In Cellular Processesmentioning
confidence: 99%